The spillover Effect of Foreign Direct Investment on Regional Growth in Iran: Spatial Econometric Analysis - Ramezan Hosseinzadeh (International Journal of Business and Development Studies, 2022)
According to the economic literature, foreign direct investment (FDI) has the main role in the growth of countries. Therefore, the main goal of present study is to examine the direct and indirect (spatial) effect of FDI on growth of GDP in different regions of Iran using the spatial econometric model. For this purpose, the data of 30 provinces of Iran during 2010-2018 has been used. The spatial weight matrix (W), is considered based on the contiguity of the regions. The results of model showed that FDI had a positive direct and spillover effects on growth of regions. Also, government spending in the regions, increase of financial credits and human capital had a direct positive effect on economic growth of the region's economy. The spillover effects of two variables, FDI and financial development, was significant. Meanwhile, the spatial (indirect) effect of FDI was positive, but the indirect (spillover) effect of financial development was negative.